2011
DOI: 10.1177/147323001103900533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Intraoperative Infusion of Dexmedetomidine or Remifentanil on Perioperative Haemodynamics, Hypnosis and Sedation, and Postoperative Pain Control

Abstract: This prospective, randomized, doubleblind study compared the effects of dexmedetomidine and remifentanil on haemodynamic stability, sedation and postoperative pain control in the postanaesthetic care unit (PACU). Fifty consecutive patients scheduled for total laparoscopic hysterectomy were randomly assigned to receive infusions of either dexmedetomidine (1 µg/kg) i.v. over 10 min followed by 0.2 -0.7 µg/kg per h continuous i.v. infusion or remifentanil (0.8 -1.2 µg/kg) i.v. over 1 min followed by 0.05 -0.1 µg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 33 publications
2
38
1
Order By: Relevance
“…Nevertheless, this meta-analysis has several limitations. First, only eight trials 3,[21][22][23]35,37,44,47 reported the source of their funding; and therefore, we did not know Fig. 6 Results of subgroup analysis of the incidence of postoperative shivering by routes of dexmedetomidine administration whether the other trials were supported by industry, which could make the design prone to show the drug in its best light.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this meta-analysis has several limitations. First, only eight trials 3,[21][22][23]35,37,44,47 reported the source of their funding; and therefore, we did not know Fig. 6 Results of subgroup analysis of the incidence of postoperative shivering by routes of dexmedetomidine administration whether the other trials were supported by industry, which could make the design prone to show the drug in its best light.…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al . in their comparative study showed significant advantage of Dexmedetomidine at dose of 1 μ g/kg bolus followed by 0.2-0.7 μ g/kg/h infusion for 24 h.[10] It is a safe sedative alternative to benzodiazepine/opioid combination in patients undergoing monitored anesthesia care for a multitude of procedures because of its analgesic, “co-operative sedation” and lack of respiratory depression properties. [11] Several findings lead to the conclusion that the major sedative and antinociceptive effects of Dexmedetomidine are attributable to its stimulation of the α-2 adrenoceptors in the locus coeruleus.…”
Section: Discussionmentioning
confidence: 99%
“…in a prospective randomized double blind study compared the effects of Dexmedetomidine and remifentanil on hemodynamic stability, sedation and post-operative pain control in PACU with the Dexmedetomidine at a dose of 1 μ g/kg IV over 10 min followed by 0.2-0.7 μ g/kg/h continuous IV infusion had a significant advantage in terms of post-operative hemodynamic stability. [10]…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effects of these sedative drugs on inflammation have been considered (1,2), and for both clinical and in vitro studies have compared the effects of these three drugs on inflammation models (3,4). Propofol and midazolam has shown anti-inflammatory properties in a variety of experimental models (1,5), while dexmedetomidine, a highly selective agonist of α2-adrenergic receptors, may have a biphasic effect on cells (6).…”
Section: Introductionmentioning
confidence: 99%